Development of MgSO4/mesoporous silica composites for thermochemical energy storage: the role of porous structure on water adsorption. (November 2022) - Liu, Xin; Wang, Haomin; Liu, Xiao; Yang, Fangming; Guan, Li; Sani, Suleiman; Sun, Chenggong; Wu, Yupeng
Abstract: Composites 'salt in porous matrix' has been considered as a promising candidate for thermal energy storage due to their large sorption capacity, energy density and high cyclic stability. In this study, novel salt composites were prepared by using different mesoporous silica with large pore size and pore volume as the porous matrices and MgSO4 via impregnation method. The results demonstrated that both MgSO4 loading level and textural properties of the porous matrices played a critical role in determining tha vapour pressure ofe water adsorption performance of salt composites. Tested at 30 °C and a vapour pressure of 25 mbar, salt composites prepared by using mesostructured cellular foam (MCF) with 3D-interconnected porous structure exhibited excellent water adsorption capacity of 50 wt% at MgSO4 loading level of 50 wt%, which was much higher than that of commercial PQ Silica. Further characterization showed that the 3D-interconnected porous structure and large pore size of MCF benefited the dispersion of salt and the reduced diffusion resistance of vapour flux inside the pores, which could effectively improve the water adsorption capacity and hydration/dehydration rate of salt composites. All the results indicated that the novel composites are expected to be a promising candidate for low temperature energy storage.